Physical and Sensory Characteristics of Guava Fruit Juice with the Addition of Cinnamon and Brown Sugar - Putra, Anak Agung Ngurah Dwi Ariesta Wijaya; Sintyadewi, Putu Rima; Yoga, Wahyu Krisna; Anggaraeni, Komang Rosa Tri (Jurnal Pijar Mipa, 2025)
The development of healthy food has grown very rapidly. Healthy food is not expensive but food that can provide good health benefits. Making fruit juice drinks from red guava can increase public interest in consuming fruit to maintain health and food security. This study aims to test the physical and sensory properties of red guava juice with the addition of cinnamon and brown sugar. This study used a Completely Randomized Design (CRD) with six treatment combinations and one control. Red guava juice, adding cinnamon and brown sugar, has a pH value ranging from 4.73-5.82 and a viscosity value ranging from 255.4 - 365.8 cps. Adding cinnamon and brown sugar affects red guava juice's pH value and viscosity. The higher the addition of cinnamon and brown sugar, the higher the pH value and viscosity. Panellists liked sample P2 with 2% cinnamon and 6% brown sugar for sensory tests.